2016
DOI: 10.1186/s12872-016-0191-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-supervised low intensity aerobic excise training on the microvascular endothelial function of patients with type 1 diabetes: a non-pharmacological interventional study

Abstract: BackgroundThe aim of the present study was to evaluate changes in microvascular density and reactivity in patients with type 1 diabetes (T1D) resulting from low intensity chronic exercise training.MethodsThis study included 22 (34 ± 7 years) consecutive outpatients with T1D and disease duration > 6 years. We used intravital video-microscopy to measure basal skin capillary density and capillary recruitment using post-occlusive reactive hyperemia (PORH) in the dorsum of the fingers. Endothelium-dependent and -in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 74 publications
0
14
2
1
Order By: Relevance
“…Nevertheless, they did not assess other markers such as oxidative stress or inflammation markers which also affect vascular function. Contrary to the observations of Roche et al, a four-week low intensity aerobic training programme in DM1 patients did not affect skin microvascular reativity, as assessed by local heating, PORH and iontophoresis of ACh and SNP [39]. On the other hand, capillary density in response to PORH, assessed by dynamic capillaroscopy, was increased in the same group of patients [39].…”
Section: The Effect Of Exercise Training In Type 1 Diabetescontrasting
confidence: 79%
“…Nevertheless, they did not assess other markers such as oxidative stress or inflammation markers which also affect vascular function. Contrary to the observations of Roche et al, a four-week low intensity aerobic training programme in DM1 patients did not affect skin microvascular reativity, as assessed by local heating, PORH and iontophoresis of ACh and SNP [39]. On the other hand, capillary density in response to PORH, assessed by dynamic capillaroscopy, was increased in the same group of patients [39].…”
Section: The Effect Of Exercise Training In Type 1 Diabetescontrasting
confidence: 79%
“…Benefits of exercise training on vascular function have been also reported in individuals with and without cardiovascular disease . For instance, our group has already reported that low‐intensity aerobic exercise training, performed at least three times per week, increased endothelial‐dependent capillary reactivity in patients with type 1 diabetes and coronary artery disease . Prior research has also demonstrated that exercise training improved endothelial function in adolescents with type 2 diabetes and chronic heart failure, compared to sedentary patients who received only standard clinical care.…”
Section: Discussionmentioning
confidence: 71%
“…In respect to cardio‐metabolic diseases, de Moraes et al . () reported that skin microvascular density and endothelium‐dependent capillary recruitment were increased in patients with diabetes after twelve weeks of exercise training performed four times per week. On the other hand, Olsen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Hodges et al (2010), for instance, observed that three exercise sessions/week for 48 weeks in postmenopausal women increased peak cutaneous endothelial-dependent vasodilation in response to acetylcholine iontophoresis measured by laser-Doppler flowmetry. In respect to cardio-metabolic diseases, de Moraes et al (2016) reported that skin microvascular density and endothelium-dependent capillary recruitment were increased in patients with diabetes after twelve weeks of exercise training performed four times per week. On the other hand, Olsen et al (2015) demonstrated that three weekly sessions of aerobic interval exercise for 12 weeks did not change systemic vascular function measured by arterial tonometry in patients with CAD.…”
Section: P-value* High Frequency Low Frequencymentioning
confidence: 99%